Physiological responses of sickle cell trait carriers during exercise - Connes, P.; Reid, H.; Hardy-Dessources, M.-D.; Morrison, E.; Hue, O. (Sports Medicine, 2008)
Growing evidence suggests that physiological responses during exercise in sickle cell trait (SCT) carriers might differ from persons with normal haemoglobin. Epidemiological and experimental results support the view that SCT carriers could be advantaged in certain anaerobic activities, but the underlying physiological and bio-cellular mechanisms remain unknown. Maximal aerobic physical fitness (i.e. maximal oxygen consumption and maximal aerobic power) is not affected by SCT; however, recent studies suggest that SCT carriers could be characterized by a lesser aerobic capacity. Discrepancies are frequently reported in the literature concerning lactate metabolism during exercise in this population. While some studies observed higher blood lactate concentration during exercise in individuals carrying SCT compared with subjects with normal haemoglobin, others described lower concentration, which suggests a paradoxical lower lactate production by exercising muscles and/or greater ability to clear circulating lactate in SCT carriers. One of the most debated topics is the clinically benign condition of SCT, particularly during strenuous exercise. SCT carriers are usually involved in physical exercise without developing medical complications; however, several authors have presented case reports of SCT carriers who have collapsed and died unexpectedly during or after exercise. Blood rheological, haemostatic and vascular adhesion mechanism abnormalities in combination with environmental factors, such as heat strain, might play a role in the occurrence of these fatal scenarios. Several physiological differences have been observed between SCT carriers and non-SCT carriers, which make it necessary to consider the former as a specific population in response to exercise.